Molecular Detection of HSV and CMV among Patients with Hematological Malignancies at the University College Hospital (UCH) Ibadan, Oyo State - Annabelle, Alimi Grace O.; Olatunji, Muideen Babatunde; Doyinsola, Afonja Olufunmilayo; Babafemi , Macaulay Oluropo; Esther JP , Ayomo Folakemi; Daramola, Kolawole Tunmise (American Journal of Biology and Natural Sciences, 2024)
Introduction: Human cytomegalovirus (CMV) and Herpes Simplex Virus (HSV) are DNA viruses from the herpesvirus family, known for their high prevalence and ability to cause significant health issues, especially in immunocompromised individuals. CMV is transmitted through various routes including saliva, sexual contact, blood, and breast milk, with a seroprevalence ranging from 30% to over 90%, influenced by factors such as age and socio-economic status.Acute CMV infections are usually mild in healthy individuals but can establish latency and chronic infection, posing severe risks for immunosuppressed patients, such as those with hematological malignancies. Similarly, HSV, which includes HSV-1 and HSV-2, is known for causing painful blisters or ulcers. HSV-1 typically causes oral infections, while HSV-2 is primarily associated with genital infections. Both types can cause severe complications in immunocompromised individuals. In patients with hematological malignancies, the immunosuppressive therapies required for treating their underlying conditions can lead to the reactivation of these viruses, causing severe complications and increasing mortality. This study aims to detect HSV and CMV in patients with hematological malignancies at the University College Hospital (UCH) Ibadan using molecular techniques. Objectives: The primary objective is to determine the prevalence of HSV and CMV in patients with hematological malignancies at UCH Ibadan. The study also aims to correlate viral infections with specific malignancies and treatments, and assess the clinical impact of these infections in the patient population. Method of Analysis: This cross-sectional study involved fifty one consenting patients with hematological malignancies. Blood samples were collected, and plasma was separated and stored at -20°C. DNA was extracted using the Da An Gene Viral DNA/RNA kit and detected using Polymerase Chain Reaction (PCR) with specific primers for HSV and CMV. The results were analyzed to determine the prevalence of these viruses and their association with clinical parameters and treatments. Results: Among the 51 patients tested, HSV-1 accounted for 19.6% of the samples, while CMV accounted for 3.9%. A prevalence of 3.9% was observed for patients with co-infection (both HSV-1 and CMV). No HSV-2 was detected. The mean age of patients was 51.96 ± 13.98 years, with a higher prevalence of male patients (64.7%) compared to females (35.3%). Patients with multiple myeloma were more frequently infected with HSV-1, while those with lymphoma had higher CMV prevalence. Symptoms like fever, weight loss, and fatigue were common, with significant numbers undergoing chemotherapy and antibiotics treatment. Conclusion: This study underscores the significant prevalence of HSV-1 and CMV among patients with hematological malignancies, highlighting the need for vigilant monitoring and management. The findings suggest a potential gender disparity and a correlation between specific malignancies and viral infections. Comprehensive treatment protocols considering the risk of viral reactivation are essential for improving patient outcomes.